Whither Studies of Asian Democratization - Törnquist, Olle (Kasarinlan: Philippine Journal of Third World Studies; Vol 12 No 1 (1996): Democratic Transitions)
What do current and future studies of Asian democratization look like? Starting off from a minimum definition of democracy that allows for different forms, scope and content, the article weaves through the early and mainstream current approaches to the study of democracy and democratization, in general, in an effort to find an answer. It next zeroes in on the relevance and usefulness of these predominant explanatory frameworks to the analysis of Asian democratization, in particular. Comparing the Philippine, Keralan, and Indonesian experiences, 11 essential themes emerge as areas for further exploration and study. These vital but comparatively neglected issues all call for a closer look at the deeper dimensions or real foundations of democratization, including the special need to focus on the problems of politicizing civil society and the so-called social capital. The paper concludes with a preliminary analytical tool for understanding such required politicization.
Keywords: Asian Democratization, Philippines, Keralan, Indonesia